Association of Previous Surgical Miscarriage with Risk of Preterm Subsequent Pregnancy in Females Presenting in a Tertiary Care Hospital: Surgical Miscarriages and Preterm Pregnancy - Gul, Yasmeen; Yousaf, Aisha; Akram, Rabia; Baber, Rubina; Khokhar, Shabana; Sultana, Bushra (Pakistan Journal of Health Sciences, 2024)
Surgical miscarriages are a common obstetric issue with potential long-term effects on subsequent pregnancies. Objective: To evaluate the association between previous surgical miscarriages and the risk of preterm birth in later pregnancies. Methods: This descriptive cross-sectional study was conducted at the Department of Obstetrics & Gynaecology, Mekran Medical College (MMC), Turbat, from November 2023 to April 2024. Data collected included age at second pregnancy, BMI, socioeconomic status, smoking status, and medical conditions such as hypertension and diabetes. Collected data were processed and analyzed using IBM SPSS, version 27.0. Results: The study included 230 patients with a history of miscarriage. Participants with ≥ 3 previous miscarriages had significantly higher odds of all-cause preterm birth (OR = 8.19, p = 0.050), spontaneous preterm birth (OR = 6.38, p = 0.005), and induced preterm birth (OR = 4.64, p < 0.001) compared to those with 1 previous miscarriage. After adjustment, those with ≥ 3 previous miscarriages had higher odds of all-cause (OR = 4.92, p < 0.001) and spontaneous preterm birth (OR = 5.79, p = 0.005), but not induced preterm birth (OR = 5.63, p = 0.050). Conclusions: Our study results revealed a significant association between a history of previous surgical miscarriages and the probability of preterm births in subsequent pregnancies. These findings underscore the need for clinical monitoring and interventions for women with a history of surgical miscarriages